Principles of engineering economy - Grant, Eugene Lodewick (John Wiley & Sons, 1982)
The Seventh edition of the standard engineering economy text and reference explains the principles and techniques needed for making decisions about the acquisition and retirement of capital goods by industry and government, as well as alternative types of financing and other applications. Arranged in four parts: basic concepts, principles, and mathematics; procedures and methods for evaluating alternatives; techniques for handling special situations; and special applications. Introduces the use of computers and spreadsheets in evaluating engineering alternatives. Includes up-to-date coverage of federal tax legislation, extensive discussions and problems dealing with personal finance, and material on handling multiple alternatives by rate of return and benefit/cost ratio methods.